Algunes dades sobre la transmissió de les vides de sants entre l'edat mitjana i l'època moderna a la Corona d'Aragó. - GARCIA SEMPERE, MARINELA (Scripta, 2019)
The lives of saints in the Middle Ages were models to follow, examples to be used in sermons and didactic or doctrinal writings. Their popularity is reflected in plastic and visual arts, in literature, and in popular culture. Through the example of the written transmission in Catalan of three lives of saints, included in the Catalan translation of the Legenda aurea, we present in this work an approach to the way in which those lives circulated individually or as part of compilations, each of which could present different versions of the same life. The repercussion of those lives survives into the Modern Age, when they take the form of compositions in verse, of plays, or of works in other literary genres.